A Literature Review on Firm Internationalization：Theoretical and Conceptual Frameworks - Huang, Jiaying (Journal of Modern Social Sciences, 2025)
This paper follows Andersen's distinction between theory and conceptual frameworks, classifying and reviewing firm internationalization studies based on their theoretical foundations. Through a systematic review of literature published in leading international business journals from 1960 to 2023, this study uniquely bridges the gap between economically oriented and process-oriented perspectives on internationalization. The paper explores the relationships among various conceptual frameworks of firm internationalization by examining their variables and conceptual structures, with particular emphasis on knowledge as a unifying construct. Unlike previous reviews that predominantly focus on either large multinational enterprises or SMEs, this paper constructs a comprehensive, integrative conceptual framework that accommodates diverse internationalization pathways. This framework facilitates theoretical dialogue and provides a foundation for future empirical research, particularly in the context of digital transformation and emerging market firms.
Keywords: Firm internationalization; Uppsala Model; Innovation-Related Model; International Entrepreneurship; Network Theory; Resource-Based Theory